Pembentukan Dan Pengembangan Paguyuban UMKM Kalirungkut Sebagai Komunitas Daerah Untuk Meningkatkan Perekonomian UMKM - Akmat Syaifudin; Supriyono Supriyono (Pusat Riset dan Inovasi Nasional, 2023)
Kalirungkut Village is an area located in Rungkut District, Surabaya City. The village has a variety of potentials that can be developed, especially the MSMEs sector as a leading potential. Based on village apparatus data, there are more than 50 MSMEs operating in the area. However, many Kalirungkut MSMEs are not well coordinated because there is no community as a forum. This has an effect on economic conditions, both for the MSMEs actors themselves and for the Kalirungkut Village. Thus, the purpose of the community service activity is to create a forum in the form of the Kalirungkut MSMEs Association which functions as a means to gather, foster, manage, and coordinate all MSMEs actors in the local village. The service method used is Participatory Rural Appraisal (PRA) which consists of three stages, namely selecting the association chairman, developing the association's management structure, as well as inaugurating and developing the association's operations. The results obtained from the service activities were the formation of the Kalirungkut MSMEs Association chaired by Ismudji Rahayuningsih and accompanied by four other administrators.